Implementing quadratic supergravity inflation - German, G; Ross, G; Sarkar, S (1999)
We study inflation driven by a slow-rolling inflaton field, characterised by a quadratic potential, and incorporating radiative corrections within the context of supergravity. In this model the energy scale of inflation is not overly constrained by the requirement of generating the observed level of density fluctuations and can have a physically interesting value, e.g. the supersymmetry breaking scale of $10^{10}$ GeV or the electroweak scale of $10^3$ GeV. In this mass range the inflaton is light enough to be confined at the origin by thermal effects, naturally generating the initial conditions for a (last) stage of inflation of the new inflationary type.